Counter hegemony of cultural art innovation against art in digital media - I Wayan Sugita; Made Setinib; Yahya Anshori (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Culture is the most critical thing when driving innovation. This paper aims to discuss the counter-hegemony of Drama Gong against modern entertainment arts today with the dynamics of openness innovation. The research method used is qualitative and uses triangulation analysis. Basic qualitative data were obtained by examining two stories of Drama Gong, namely: (1) Angling Dharma (the 1980s) and (2) Jayaprana (2020). Data were collected through observation, document review, and interviews with artists and art observers of the Drama Gong culture of Bali. Qualitative descriptive analysis was carried out by applying the theory of semiotics and the theory of symbolic interaction. The results showed that to maintain its existence since the 1980s Drama Gong performance art has been revitalized as a form of counter-hegemony to today's modern entertainment arts. The counter-hegemony concerns three things, namely: (1) the innovation of Drama Gong performance art, (2) the application of new technology to support the packaging and performance of the Drama Gong, and (3) efforts to maintain the function of the Drama Gong as a way to teach Balinese culture.
Keywords: 650; Drama Gong; hegemony; entertainment; cultural art innovation; digital media